2023
DOI: 10.2174/1573401318666221003104005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Enzymatic Hydrolysis of Protein from Different Food Sources and Potential Separation Techniques

Abstract: Enzymatic hydrolysis (EH) of proteins relies essentially upon the enhancement of the functional and nutritional properties of proteins, such as antioxidant activity, solubility, oil holding capacity, water holding capacity, emulsification, foaming properties, and sensory properties. There is a big challenge for protein separation and purification due to the high production cost, the large number of amino acids, and the complex biological system of proteins. These biological structures are always presented in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…Resins present different adsorption characteristics, which may be due to different adsorption and desorption mechanism (Mohammad et al, 2023; Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resins present different adsorption characteristics, which may be due to different adsorption and desorption mechanism (Mohammad et al, 2023; Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Resins present different adsorption characteristics, which may be due to different adsorption and desorption mechanism (Mohammad et al, 2023;Wang et al, 2017). Results showed that the resins presented higher adsorption capacity at lower pHs.…”
Section: Static Adsorption and Desorptionmentioning
confidence: 99%